ANALISIS SEMIOTIK CHARLES SANDERS PEIRCE DALAM FILM SPOTLIGHT - Deni Rahman; Jihan Fernanda (Communicative : Jurnal Dakwah dan Komunikasi, 2023)
This research aims to analyze the film "Spotlight." This research uses a qualitative method with data collection techniques including primary and secondary data. The data analysis technique used in this research is a qualitative descriptive analysis technique. The semiotic method used for this research is Charles Sanders Peirce's Semiotics. The results of this research indicate that the meaning of the message of journalism symbols according to Charles Sanders Peirce's semiotic analysis in the film "Spotlight" is that a journalist must have 1) a high sense of curiosity 2) ethics when digging for a story, 3) the principle of balance, 4) objectivity, 5) a notebook or recorder as a tool to remember acquired information, and 6) the courage to conduct reporting and data research to be used as news.